(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
BACKGROUND: Salivary gland swellings can result from tumors, an inflammatory process or cyst. Fine needle aspiration cytology(FNAC) is a diagnostic tool for evaluating neoplastic and non neoplastic swelling of salivary gland. The objective of this study was to evaluate the diagnostic accuracy and sensitivity and specificity of fine needle aspiration cytology in numerous salivary gland lesions and with its histopathological correlation. METHOD: The study was conducted in department of pathology; Amc met medical college, Ahmedabad, Gujarat, India, for duration of 1 year from January 2019 to January 2020. During the study period 44 cases of fine needle aspiration cytology of salivary gland lesions were performed. Formalin fixed (10%), surgically resected specimens were received and prepared for histopathological salivary gland lesion diagnosis. RESULT: During the study period 998 FNAC were undertaken of which 44 FNAC were of salivary gland swelling. Correlation of cytology from FNAC with histopathology tissue was possible in 9 cases, for which FNAC data was available. 62 % were from male and 38 % were from female patients. The age of patient ranged from 8 to 85 Years. 15 cases were benign swellings. 8 cases were malignant, 7 cases were cysts and 14 cases had an inflammatory etiology. CONCLUSION: Fine needle aspiration cytology (FNAC) is highly sensitive and specific procedure for diagnosis of salivary gland lesions.